A temperature-resistant and salt-resistant active wrinkle-shaped mesoporous oil displacement system, a preparation method and application thereof

CN122810796APending Publication Date: 2026-09-25CHINA NAT OFFSHORE OIL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611117413.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-09-25

AI Technical Summary

Benefits of technology

更优选地,所述驱油体系使岩心表面接触角从>110°降至≤20°,提高采收率≥45%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application discloses a kind of temperature-resistant salt-resistant active pleated mesoporous nanometer oil displacement system and preparation and application.The application first prepares nanometer silicon dioxide with radial isolated pleated mesoporous structure by template method, and its surface is rich in active hydroxyl group;Then it is modified and grafted with betaine type functional monomer in turn by silane coupling agent, to obtain functionalized pleated mesoporous nanometer material;At the same time, betaine type hydrophobic association polymer is prepared by copolymerization of hydrophilic monomer, betaine type functional monomer and hydrophobic monomer;Finally, functionalized nanometer material and polymer are compounded in water, and the oil displacement system is obtained.The oil displacement system has excellent temperature resistance, salt resistance, shear resistance and dispersion stability under high temperature and high salt conditions, can effectively reverse the wettability of core surface, significantly improve oil recovery, and is suitable for the field of tertiary oil recovery of high temperature and high salt reservoir.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a temperature- and salt-resistant active pleated mesoporous nano-oil displacement system, its preparation method, and its application, belonging to the field of oilfield development technology. Background Technology

[0002] The era of "easy-to-extract oil" is fading away. With the increasing depth and breadth of oilfield development, more complex oil reservoirs are emerging, making it more difficult to tap their potential. Conventional nanofluids, polyacrylamide and their derivatives have reached a bottleneck in terms of temperature and / or salt resistance. There is an urgent need to develop new materials and oil displacement systems to significantly improve the recovery rate of high-temperature and high-salinity oil reservoirs.

[0003] The success of nanotechnology in other areas of the petroleum industry has inspired enhanced oil recovery (EOR) technologies. By incorporating thermally stable, high-specific-surface-area inorganic nanomaterials into polymer solutions, oil recovery can be significantly improved by altering core wettability, improving solution rheological properties, and enhancing the system's temperature, salt, and shear resistance. In recent years, nanomaterials with unique mesoporous structures have attracted widespread attention from researchers. Mesoporous nanomaterials possess unique morphological characteristics and physicochemical properties, such as high specific surface area, a high proportion of hydroxyl groups, and high active sites, resulting in rich surface chemical properties and improved surface functionalization efficiency. Their unique properties can significantly influence the interaction between nanoparticles and polymers, increasing polymer molecule rigidity, inhibiting polymer hydrolysis, protecting the polymer backbone, and simultaneously enhancing intermolecular interactions, promoting the formation of a strong network structure, empowering the polymer, enhancing polymer performance, and significantly improving the system's temperature, salt, and shear resistance. Therefore, mesoporous nano-silica is an ideal candidate material for improving the recovery of high-temperature, high-salinity oil reservoirs in nanomaterial / polymer flooding systems.

[0004] To address the aforementioned needs, a temperature- and salt-resistant active pleated mesoporous nano-oil displacement system was developed to enhance oil recovery under high-temperature and high-salt conditions. Summary of the Invention

[0005] The purpose of this invention is to provide a temperature- and salt-resistant active wrinkled mesoporous nano-oil displacement system. The wrinkled mesoporous nanomaterials provided by this invention have the characteristics of special wrinkled mesoporous structure, high specific surface area, high proportion of hydroxyl groups, high active sites and low density. The resulting active wrinkled mesoporous nano-fluid displacement system has better temperature and salt resistance and is effective in improving oil recovery after oil displacement.

[0006] The temperature-resistant and salt-resistant active wrinkled mesoporous nano-oil displacement system provided by the present invention comprises functionalized wrinkled mesoporous nanomaterials, betaine-type hydrophobic associative polymers and water; The functionalized wrinkled mesoporous nanomaterial is obtained by sequentially modifying the wrinkled mesoporous nanomaterial with a silane coupling agent and grafting it with a functional monomer, wherein the functional monomer is a betaine-type functional monomer. The betaine-type hydrophobic associative polymer is a polymer copolymerized from hydrophilic monomers, betaine-type functional monomers, and hydrophobic monomers.

[0007] The wrinkled mesoporous nanomaterial exhibits a sheet-like or layered wrinkled morphology on its surface, with isolated and unconnected pores, and a radial pore structure. The particle size of the wrinkled mesoporous nanomaterial is 50-420 nm, and its specific surface area is 150-1100 m². 2 ·g -1 The pore volume is 0.07-2 cm³. 3 ·g -1 .

[0008] The functionalized wrinkled mesoporous nanomaterial has a mass concentration of 0.1-0.5% in the mesoporous nano-oil displacement system, preferably 0.2-0.3%, and more preferably 0.25%; the betaine-type hydrophobic associating polymer has a mass concentration of 1000-2000 mg·L in the mesoporous nano-oil displacement system. - ¹, preferably 1200-1800 mg·L - ¹, more preferably 1500 mg·L -1 .

[0009] This invention also provides a method for preparing the aforementioned temperature-resistant and salt-resistant active wrinkled mesoporous nano-oil displacement system, comprising the following steps: (1) Add template agent and catalyst to water, stir, and then add tetraethyl silicate and oil phase mixed solution and co-solvent in sequence. After heating and reaction, centrifuge, wash, dry and calcinate to obtain wrinkled mesoporous nanomaterials. (2) Disperse the wrinkled mesoporous nanomaterial in water, add silane coupling agent to carry out modification reaction, and obtain modified wrinkled mesoporous nanomaterial; disperse the modified wrinkled mesoporous nanomaterial in water, add functional monomer, carry out graft polymerization reaction in the presence of initiator, and obtain functionalized wrinkled mesoporous nanomaterial after separation, washing and drying. (3) The hydrophilic monomer, betaine-type functional monomer and hydrophobic monomer are copolymerized in water in the presence of an initiator in the presence of a surfactant. After precipitation, drying and granulation, a betaine-type hydrophobic associative polymer is obtained. (4) The functionalized wrinkled mesoporous nanomaterial is dispersed in water to form a suspension, the betaine-type hydrophobic associative polymer is dissolved in water to form a polymer solution, and the polymer solution is added to the suspension and mixed to obtain the active wrinkled mesoporous nano-oil displacement system.

[0010] The conditions in step (1) are as follows: The template agent is selected from one or more of hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, hexadecylpyridine bromide, and hexadecylpyridine chloride, preferably hexadecyltrimethylammonium bromide; The template agent has a mass fraction of 1-5%, preferably 2-4%, and more preferably 3%; The catalyst is selected from one or more of ammonia, urea, methylamine, n-propylamine, ethylenediamine, 1,2-propanediamine, 1,3-propanediamine, ethanolamine, formamide, and acetamide, preferably urea; The catalyst has a mass fraction of 1-4%, preferably 2-3%, and more preferably 2.4%. The oil phase is selected from one or more of benzene, toluene, p-xylene, styrene, chlorobenzene, cyclohexane, n-hexane, n-octane, and decane, preferably p-xylene; The mass fraction of the tetraethyl silicate is 5-40%, preferably 20-30%, and more preferably 25%. The co-solvent is selected from one or more of methanol, ethanol, ethylene glycol, isopropanol, n-butanol, n-pentanol, and octanol, preferably n-pentanol; The mass fraction of the co-solvent is 1-10%, preferably 4-8%, and more preferably 6%; The stirring speed is 500-2500 r·min -1 Preferably 700-1200 r·min -1 More preferably 1000 r·min -1 ; The reaction temperature is 60-100℃, preferably 85℃; The reaction time is 1-15 h, preferably 6 h; The calcination temperature is 500-600℃, and the calcination time is 4-8 h.

[0011] The conditions in step (2) are as follows: The mass fraction of the wrinkled mesoporous nanomaterial is 0.05-0.3%, preferably 0.05-0.15%, and more preferably 0.1%. The silane coupling agent is selected from one of vinyltris(β-methoxyethoxy)silane, vinyltrimethoxysilane, vinyltriethoxysilane, and γ-methacryloyloxypropyltrimethoxysilane, preferably vinyltriethoxysilane; The mass fraction of the silane coupling agent is 1-3%, preferably 1.6-2%, and more preferably 1.8%; The temperature of the modification reaction is 60-100℃, preferably 70-90℃, and more preferably 80℃; The modification reaction takes 0.5-5 h, preferably 1-3 h, and more preferably 2 h; The modified wrinkled mesoporous nanomaterial has a mass fraction of 0.05-0.25%, preferably 0.1-0.2%, and more preferably 0.15%. The functional monomer is selected from one of N,N'-dimethyl(methacrylamide ethyl)ammonium propanesulfonate, N,N'-dimethyl(methacryloyloxyethyl)ammonium propanesulfonate, and 3-(N-allyl-N-methylamino)propane-1-sulfonate, preferably N,N'-dimethyl(methacryloyloxyethyl)ammonium propanesulfonate. The mass fraction of the functional monomer is 0.05-0.15%, preferably 0.06-0.1%, and more preferably 0.08%; The initiator has a mass fraction of 0.01-0.05%, preferably 0.02-0.04%, and more preferably 0.03%. The temperature of the graft polymerization reaction is 30-60℃, preferably 40-50℃, and more preferably 45℃; The graft polymerization reaction takes 1-6 hours, preferably 3-5 hours, and more preferably 4 hours.

[0012] The conditions in step (3) are as follows: The hydrophilic monomer is selected from one of acrylamide, methacrylamide, N,N-dimethylacrylamide, and N,N'-methylenebisacrylamide, preferably N,N-dimethylacrylamide; The betaine-type functional monomer is selected from one of N,N'-dimethyl(methacrylamide ethyl)ammonium propanesulfonate, N,N'-dimethyl(methacryloyloxyethyl)ammonium propanesulfonate, and 3-(N-allyl-N-methylamino)propane-1-sulfonate, preferably N,N'-dimethyl(methacryloyloxyethyl)ammonium propanesulfonate. The hydrophobic monomer has a carbon chain length of C8-C9. 18 The acrylate hydrophobic monomer is preferably selected from one of n-octyl acrylate, decyl acrylate, tetradecyl acrylate, hexadecyl acrylate, octadecyl acrylate, undecyl methacrylate, lauryl methacrylate, and octadecyl methacrylate, and more preferably n-octyl acrylate; The molar ratio of the hydrophilic monomer, betaine-type functional monomer, and hydrophobic monomer is (80-95):(5-20):(0.5~1.5), preferably 89:10:1; The total mass fraction of the monomer is 15-35%, preferably 20-30%, and more preferably 25%; The surfactant is selected from one of sodium dodecyl sulfonate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, polyethylene glycol octylphenyl ether, and polyoxyethylene sorbitan fatty acid ester, preferably sodium dodecyl sulfate; The surfactant has a mass fraction of 1-5%, preferably 3-4%, and more preferably 3.5%. The initiator has a mass fraction of 0.01-0.04%, preferably 0.01-0.03%, and more preferably 0.02%. The temperature of the copolymerization reaction is 30-80℃, preferably 40-60℃, and more preferably 50℃; The copolymerization reaction takes 2-6 hours, preferably 3-5 hours, and more preferably 4 hours.

[0013] The functionalized wrinkled mesoporous nanomaterials involved in the temperature-resistant and salt-resistant active wrinkled mesoporous nano-oil displacement system of this invention also fall within the protection scope of this invention: comprising a wrinkled mesoporous silica matrix and betaine-type functional monomer segments grafted onto the surface of the matrix. The surface of the matrix exhibits a lamellar or layered folded morphology, with isolated and unconnected pores, and the pore structure is radial; the particle size of the matrix is ​​50-300 nm, and the specific surface area is 300-1100 m². 2 ·g -1 The pore volume is 0.5-2 cm³. 3 ·g -1 The pore length of the mesopores is 10-200 nm; The betaine-type functional monomer is selected from N,N'-dimethyl(methacrylamide ethyl)ammonium propanesulfonate, N,N'-dimethyl(methacryloyloxyethyl)ammonium propanesulfonate, or 3-(N-allyl-N-methylamino)propane-1-sulfonate.

[0014] The betaine-type hydrophobic associative polymer involved in the temperature-resistant and salt-resistant active wrinkled mesoporous nano-oil displacement system of this invention also falls within the protection scope of this invention: it includes structural unit A, structural unit B and structural unit C. The structural unit A is derived from a hydrophilic monomer, which is selected from acrylamide, methacrylamide, N,N-dimethylacrylamide or N,N'-methylenebisacrylamide; The structural unit B is derived from a betaine-type functional monomer, which is selected from N,N'-dimethyl(methacrylamide ethyl)ammonium propanesulfonate, N,N'-dimethyl(methacryloyloxyethyl)ammonium propanesulfonate or 3-(N-allyl-N-methylamino)propane-1-sulfonate; The structural unit C is derived from a hydrophobic monomer, which has a carbon chain length of C8~C8. 18 acrylate hydrophobic monomers; The molar ratio of structural unit A, structural unit B and structural unit C is (80-95):(5-20):(0.5-1.5).

[0015] The temperature- and salt-resistant active pleated mesoporous nano-oil displacement system of this invention can be used for oil displacement in high-temperature and high-salinity reservoirs to improve oil recovery. The high-temperature and high-salinity reservoirs have a temperature of 80-150℃ and a salinity of 10,000-50,000 mg·L⁻¹. -1 ; Preferably, the oil displacement system is at 120°C and 24671 mg·L⁻¹. -1 Viscosity retention ≥80%, shear recovery ≥85%, and absolute value of Zeta potential ≥40 mV under the specified conditions; More preferably, the oil displacement system reduces the core surface contact angle from >110° to ≤20°, thereby increasing the oil recovery rate by ≥45%.

[0016] The active, wrinkled, mesoporous nano-oil displacement system provided by this invention uses nano-silica (WMNs) with a radially isolated wrinkled mesoporous structure as its core material. Its hydroxyl content is 3.85-8.69 times that of conventional nano-SiO2, and the functional monomer grafting rate is increased by 1.31-2.27 times. At 120℃ and 24671 mg·L⁻¹... -1 Under high temperature and high salinity conditions, the system exhibits a viscosity retention rate of 83.1% (reaching 33.67 mPa·s), a shear recovery rate of 88.16%, and an absolute Zeta potential of 42.6 mV, demonstrating significantly superior overall performance compared to the conventional SiO2 system. Oil displacement experiments show that this system can reduce the core contact angle from 119° to 15°, increasing oil recovery by 49.41%, a 21.50 percentage point improvement over the SiO2 / PASO system. This invention achieves viscosity enhancement, temperature resistance, salt resistance, shear resistance, and high-efficiency oil displacement under extreme reservoir conditions through innovative material microstructure, possessing significant industrial application value. Attached Figure Description

[0017] Figure 1 The images shown are scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the wrinkled mesoporous nanomaterials in Example 1 of this invention.

[0018] Figure 2 The effect of nanomaterial concentration on the apparent viscosity of the oil displacement systems in Example 1 and Comparative Examples 1-4 of this invention.

[0019] Figure 3 The effect of NaCl concentration on the apparent viscosity of the oil displacement systems in Example 1 and Comparative Examples 1-4 of this invention.

[0020] Figure 4 The effect of temperature on the apparent viscosity of the oil displacement systems in Examples 1 and 1-4 of this invention.

[0021] Figure 5 The shear recovery curves are for the oil displacement systems of Embodiment 1 and Comparative Examples 1-4 of the present invention.

[0022] Figure 6 These are contact angle images of the core surfaces after treatment with the oil displacement systems of Embodiment 1 and Comparative Examples 1-4 of the present invention.

[0023] Figure 7 The results are from the core displacement experiment of the oil displacement system in Example 1 of this invention. Detailed Implementation

[0024] The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto. The raw materials used in the embodiments were purchased from Shanghai Maclean Biochemical Technology Co., Ltd.

[0025] Example 1: Preparation of a temperature- and salt-resistant active wrinkled mesoporous nano-oil displacement system (1) Add 3g of hexadecyltrimethylammonium bromide and 2.4g of urea to 100 mL of deionized water, place the mixture in a 500 mL three-necked flask equipped with a condenser and a thermometer, and heat at 1000 r·min at room temperature. -1 Stir for 30 minutes; then, using a constant pressure dropping funnel, add 25 mL of a mixed solution of tetraethyl orthosilicate and 100 mL of p-xylene dropwise to the three-necked flask, stirring for 30 minutes after the addition is complete; continue to add 6 g of n-pentanol, stirring for 30 minutes, then heat the reaction mixture to 85°C and maintain a constant pressure of 1000 r·min⁻¹. -1 The reaction was carried out under stirring for 6 h. After cooling, the initial product was separated by centrifugation and washed several times with water and ethanol. After drying at 80 °C for 12 hours, the product was calcined at 550 °C for 6 hours to remove hexadecyltrimethylammonium bromide, yielding the wrinkled mesoporous nanomaterial WMNs.

[0026] (2) 0.1 g of wrinkled mesoporous nanomaterials were dispersed in deionized water, followed by the addition of 1.9 g of silane coupling agent (vinyltriethoxysilane). The mixture was ultrasonically dispersed for at least 30 min, and the pH of the system was adjusted to weakly acidic. The mixture was then reacted at 80 °C for 2 h to obtain modified wrinkled mesoporous nanoparticles. Unreacted silane coupling agent was removed using a rotary evaporator. 0.3 g of modified wrinkled mesoporous nanomaterials were dispersed in 200 mL of deionized water and placed in a 500 mL three-necked flask. 0.08% (w / w) of methacryloylethyl sulfobetaine (SBMA) was added, and the mixture was ultrasonically dispersed at room temperature for 15 min. The three-necked flask was then placed in a constant temperature water bath and heated to 45 °C. 0.03% of the initiator AIBA was injected into the reaction mixture using a syringe. The mixture was reacted for 4 h and then cooled. The reaction was carried out at 3000 r·min. -1 The material was centrifuged, washed with ethanol three times or more, and then dried in a vacuum drying oven at 60°C to obtain functionalized wrinkled mesoporous nanomaterials (SWMNs).

[0027] (3) Weigh acrylamide (AM) and methacryloyl ethyl sulfobetaine (SBMA) monomers in a molar ratio of 89:10, dissolve them in 100 mL of deionized water, and place the solution in a 250 mL three-necked flask. Then add 1 mol% of the hydrophobic monomer and 3.5 g of sodium dodecyl sulfate (SDS), stir for at least 30 min, and place the three-necked flask in a constant temperature water bath. At room temperature, purge with N2 for half an hour to remove oxygen from the reaction solution. After heating to 50 °C, inject 0.02% of the initiator AIBA using a pipette, while maintaining the purge with N2 during the reaction. Then seal the three-necked flask and react for 4 h to obtain a white transparent colloid. After removing the colloid, cut it into small pieces with scissors, soak it in anhydrous ethanol for dehydration and precipitation, dry the precipitate in a vacuum drying oven, and granulate it to obtain the product PASO.

[0028] (4) Add 0.25 g of functionalized wrinkled mesoporous nanomaterials to 50 mL of deionized water and sonicate continuously for 30 min to prepare a suspension of functionalized wrinkled mesoporous nanomaterials. Then, dissolve 0.15 g of polymer powder PASO in 50 mL of deionized water. Finally, add the polymer solution to the suspension of functionalized wrinkled mesoporous nanomaterials and stir gently for 48 h to obtain the active wrinkled mesoporous nano-oil displacement system SWMNs / PASO, wherein the mass concentration of functionalized wrinkled mesoporous nanomaterials is 0.25% and the mass concentration of polymer powder PASO is 1500 mg·L⁻¹. -1 .

[0029] Example 2: Preparation of a temperature- and salt-resistant active wrinkled mesoporous nano-oil displacement system As described in Example 1, the only difference is that the template agent used in the synthesis of the wrinkled mesoporous nanomaterial WMNs is hexadecyl bromopyridine; the other steps and conditions are the same as in Example 1.

[0030] Example 3: Preparation of a temperature- and salt-resistant active wrinkled mesoporous nano-oil displacement system As described in Example 1, except that the catalyst used in the synthesis of the wrinkled mesoporous nanomaterial WMNs is ethylenediamine; the other steps and conditions are the same as in Example 1.

[0031] Example 4: Preparation of a temperature- and salt-resistant active wrinkled mesoporous nano-oil displacement system As described in Example 1, except that the mass fraction of the catalyst used in the synthesis of the wrinkled mesoporous nanomaterial WMNs was 2%; the other steps and conditions were the same as in Example 1.

[0032] Example 5: Preparation of a temperature- and salt-resistant active wrinkled mesoporous nano-oil displacement system As described in Example 1, except that the co-solvent used in the synthesis of the wrinkled mesoporous nanomaterial WMNs is ethylene glycol; the other steps and conditions are the same as in Example 1.

[0033] Example 6: Preparation of a temperature- and salt-resistant active wrinkled mesoporous nano-oil displacement system As described in Example 1, except that the mass fraction of the co-solvent used in the synthesis of the wrinkled mesoporous nanomaterial WMNs is 3%; the other steps and conditions are the same as in Example 1.

[0034] Example 7: Preparation of a temperature- and salt-resistant active wrinkled mesoporous nano-oil displacement system As described in Example 1, except that the stirring speed during the synthesis of the wrinkled mesoporous nanomaterial WMNs was 1500 r·min. -1 Other steps and conditions are the same as in Example 1.

[0035] Example 8: Preparation of a temperature- and salt-resistant active wrinkled mesoporous nano-oil displacement system As described in Example 1, except that the reaction temperature during the synthesis of the wrinkled mesoporous nanomaterial WMNs is 60°C; the other steps and conditions are the same as in Example 1.

[0036] Example 9: Preparation of a temperature- and salt-resistant active wrinkled mesoporous nano-oil displacement system As described in Example 1, except that the reaction time in the synthesis of the wrinkled mesoporous nanomaterial WMNs was 4 h; the other steps and conditions were the same as in Example 1.

[0037] Comparative Example 1: Preparation of a temperature- and salt-resistant active wrinkled mesoporous nano-oil displacement system As described in Example 1, the only difference is that the prepared wrinkled mesoporous nanomaterials WMNs were not modified or functionalized and were used directly to construct the system; the other steps and conditions were the same as in Example 1.

[0038] Comparative Example 2: Preparation of a temperature- and salt-resistant active wrinkled mesoporous nano-oil displacement system As described in Example 1, the difference is that the template agent mass fraction in the synthesis process of the wrinkled mesoporous nanomaterial WMNs is 2%, and the wrinkled mesoporous nanomaterial WMNs are not modified or functionalized, but are used directly to construct the system; other steps and conditions are the same as in Example 1.

[0039] Comparative Example 3: Preparation of a temperature- and salt-resistant active wrinkled mesoporous nano-oil displacement system As described in Example 1, the difference is that the amount of tetraethyl silicate used in the synthesis of the wrinkled mesoporous nanomaterial WMNs is 10 mL, and the wrinkled mesoporous nanomaterial WMNs is not modified or functionalized, but is used directly to construct the system; other steps and conditions are the same as in Example 1.

[0040] Comparative Example 4: Preparation of a temperature- and salt-resistant active wrinkled mesoporous nano-oil displacement system As described in Example 1, the difference is that the nanomaterial used in constructing the oil displacement system is ordinary nano-silica with a diameter of 80±5nm, and the nano-silica is not modified or functionalized. Other steps and conditions are the same as in Example 1.

[0041] Comparison of the properties of wrinkled mesoporous nanomaterials in Experimental Example 1, Examples 1-9, and Comparative Examples 2-4 Particle size analysis and N2 adsorption-desorption tests were performed on the wrinkled mesoporous nanomaterials in Examples 1-9 and Comparative Examples 2-3, and on the nano-silica in Comparative Example 4. The results are shown in Table 1. Scanning electron microscopy and transmission electron microscopy analyses were performed on the wrinkled mesoporous nanomaterials in Example 1. The results are shown in Table 1. Figure 1 As shown.

[0042] As can be seen, the main component of the wrinkled mesoporous nanomaterials WMNs prepared in Example 1 is SiO2, with hydroxyl groups on the surface, exhibiting amorphous characteristics. The particle size is 80 ± 5 nm, and the surface displays a unique "plate / layer" wrinkled morphology. The pores are isolated from each other and not connected, separated by sheet-like silica walls. The pore structure of the nanomaterial is radial, with SiO2 becoming more densely aggregated closer to the center. The specific surface area is 1094.75 m². 2 ·g -1 It is approximately 7.38 times larger than SiO2 in Comparative Example 4, with a pore volume of 1.862 cm³. 3 ·g -1 .

[0043] Table 1 Properties of wrinkled mesoporous nanomaterials

[0044] use 29 Si MAS NMR was used to quantitatively study the hydroxyl groups on the surface of the wrinkled mesoporous nanomaterials in Example 1 and Comparative Examples 2-3, and the nano-silica in Comparative Example 4. The results are shown in Table 2. It was found that the proportion of hydroxyl groups on the surface of the wrinkled mesoporous nanomaterials WMNs was much higher than that of SiO2. The wrinkled mesoporous nanomaterials in Example 1 were almost 8.69 times that of the conventional nano-SiO2 in Comparative Example 4.

[0045] Table 2 Number of hydroxyl groups on the surface of nanomaterials

[0046] Evaluation of viscosity-enhancing performance of oil displacement systems in Experimental Example 2, Example 1, and Comparative Examples 1-4 The viscosity of the oil displacement system was measured using a Brookfield DV-II rotational viscometer, with the drill speed set to 6 r·min. -1 . Figure 2 To illustrate the effect of nanomaterial concentration on the apparent viscosity of the oil displacement systems in Examples 1 and Comparative Examples 1-4, the apparent viscosity results of the oil displacement systems in Examples 1 and Comparative Examples 1-4 when the nanomaterial concentration is 0.25% are shown in Table 3.

[0047] Table 3 and Figure 2 The results show that the wrinkled mesoporous nanomaterials WMNs prepared in this invention have a much higher viscosity-enhancing ability than conventional nano-SiO2. Compared with the SiO2 / PASO oil displacement system in Comparative Example 4, the viscosity of the WMNs / PASO oil displacement system in Comparative Example 1 increased by 10.41 mPa·s, and the viscosity of the WMNs / PASO oil displacement system in Example 1 increased by 16.47 mPa·s. Compared with conventional nano-SiO2, WMNs have a higher proportion of hydroxyl groups on the surface and mesoporous inner walls, thus possessing a high proportion of active sites, increasing the number of nodes in the three-dimensional network structure. At low concentrations, they act as bridges connecting multiple polymer molecules, producing similar intermolecular association, thereby significantly increasing the viscosity of the oil displacement system.

[0048] Table 3 Apparent viscosity of the oil displacement system (25 °C)

[0049] Evaluation of the temperature resistance, salt resistance, shear resistance, and dispersion stability of the oil displacement systems in Experimental Example 3, Example 1, and Comparative Examples 1-4 Figure 3 and Figure 4 The effects of NaCl concentration and temperature on the apparent viscosity of the oil displacement systems in Example 1 and Comparative Examples 1-4 are shown, respectively. Figure 5Table 4 shows the shear recovery curves of the oil displacement systems of Examples 1 and Comparative Examples 1-4 under high temperature and high salinity conditions (120℃, 24671 mg·L⁻¹). -1 Median particle size and Zeta potential after 7 days of aging.

[0050] The above results indicate that the active, wrinkled, mesoporous nano-oil displacement system SWMNs / PASO prepared in this invention exhibits stronger salt viscosity-enhancing properties, temperature resistance, shear resistance, and dispersion stability. (120℃, 24671 mg·L⁻¹) -1 Under these conditions, the viscosity retention rate reached 83.1%, and the viscosity remained at 33.67 mPa·s, which is 2.82 times that of SiO2 / PASO and 1.29 times that of WMNs / PASO. SWMNs significantly increased the density and strength of the PASO network structure, improved the viscoelasticity of the polymer solution, thereby protecting the polymer chains from shearing and exhibiting a faster (14 min) and higher (88.16%) shear recovery rate. Even at 120℃, the viscosity retention rate was 24671 mg·L⁻¹. -1 After aging for 7 days under high temperature and high salt conditions, SWMNs can still be stably dispersed with a uniform particle size distribution (164nm), and no obvious stratification phenomenon was observed in the SWMNs / PASO oil displacement system. The absolute value of the Zeta potential is 42.6 mV.

[0051] Table 4 Median particle size and Zeta potential of the oil displacement system

[0052] Evaluation of core contact angle of oil displacement systems in Experimental Example 4, Example 1, and Comparative Examples 1-4 First, the cut core samples were polished with sandpaper of varying grits from large to small until the core surface was relatively flat and smooth. After rinsing several times with deionized water, the cores were dried and ready for use. Then, crude oil aging pretreatment was performed. The pretreated core samples were completely immersed in the oil displacement system for 7 days of aging, and then dried at 60°C. Next, using a contact angle measuring instrument, droplets were placed on the surface of the core samples treated with nanofluids using a micropipette. The surface of the rock and the morphology of the droplets were magnified using measurement software. Finally, the droplet photographs were taken under light source using the camera provided with the instrument, and the contact angle was measured. This operation was repeated 3 times, and the arithmetic mean was taken.

[0053] Table 5 shows the water phase contact angles on the core surfaces after treatment with the oil displacement systems of Example 1 and Comparative Examples 1-4. Figure 6 Images showing the water phase contact angles on the core surfaces after treatment with the oil displacement systems of Examples 1 and 1-4.

[0054] The above results indicate that the active, wrinkled, mesoporous nano-displacement system SWMNs / PASO prepared in Example 1 can reverse the wettability of the core surface, reducing the contact angle from 119° to 15°. Compared to the SiO2 / PASO displacement system and the WMNs / PASO displacement system in Comparative Example 1, the contact angle of the SWMNs / PASO displacement system is reduced by 69° and 18°, respectively.

[0055] Table 5. Water phase contact angles on core surfaces after oil displacement system treatment

[0056] Core displacement experiments of oil displacement systems in Experiments 5, 1, 9, 10, and 11 cemented rock core ( After drying, the core samples (2.5 cm × 10 cm) were used to determine the permeability and porosity using a porosimeter. Subsequently, the core was subjected to water flooding using a core displacement experimental setup at an injection rate of 0.5 mL. min -1 Then, at 120°C, 30 PV of crude oil was injected into the core until the water cut of the produced water was less than 1%. (0.5 mL) min -1 At a given injection rate, the core was first water-flooded until the produced fluid water cut reached over 95%, followed by the injection of a 0.5 PV nano-displacement system, and finally, subsequent waterflooding was performed until the water cut reached over 95%. Changes in injection pressure, water cut, and recovery rate were recorded throughout the process.

[0057] The results of core displacement experiments for the oil displacement systems in Examples 1 and 1-4 are shown in Table 6. Figure 7 The results are from the core displacement experiment of the oil displacement system in Example 1 of this invention.

[0058] The above results indicate that the active, wrinkled, mesoporous nano-displacement system SWMNs / PASO prepared in Example 1 of this invention can improve oil recovery by 49.41%, which is 21.50% higher than the SiO2 / PASO system in Comparative Example 4 and 5.76% higher than the SWMNs / PASO system in Comparative Example 1. The SWMNs / PASO system preferentially enters the mainstream channel, establishing seepage resistance and expanding the subsequent fluid sweep range. The nanomaterials spontaneously adsorb onto the core surface, generating wedge-shaped separation pressure, achieving wetting reversal, and improving oil washing efficiency. The SWMNs / PASO system improves oil recovery by pushing clustered, plunger-like residual oil, carrying lone droplet-like residual oil, pulling out blind-end residual oil, and scraping out film-like residual oil.

[0059] Table 6 Results of core displacement experiments for the oil displacement system

Claims

1. A temperature-resistant and salt-resistant active wrinkled mesoporous nano-oil displacement system, comprising functionalized wrinkled mesoporous nanomaterials, betaine-type hydrophobic associative polymers, and water; The functionalized wrinkled mesoporous nanomaterial is obtained by sequentially modifying the wrinkled mesoporous nanomaterial with a silane coupling agent and grafting it with a functional monomer, wherein the functional monomer is a betaine-type functional monomer. The betaine-type hydrophobic associative polymer is a polymer copolymerized from hydrophilic monomers, betaine-type functional monomers, and hydrophobic monomers.

2. The mesoporous nano-displacement oil system according to claim 1, characterized in that: The wrinkled mesoporous nanomaterial exhibits a sheet-like or layered wrinkled morphology on its surface, with isolated and unconnected pores, and a radial pore structure. The particle size of the wrinkled mesoporous nanomaterial is 50-420 nm, and its specific surface area is 150-1100 m². 2 ·g -1 The pore volume is 0.07-2 cm³. 3 ·g -1 .

3. The mesoporous nano-displacement oil system according to claim 1 or 2, characterized in that: The functionalized wrinkled mesoporous nanomaterials are present at a mass concentration of 0.1-0.5% in the mesoporous nano-oil displacement system; the betaine-type hydrophobic associative polymer is present at a mass concentration of 1000-2000 mg·L in the mesoporous nano-oil displacement system. -1 .

4. A method for preparing the temperature-resistant and salt-resistant active wrinkled mesoporous nano-oil displacement system according to any one of claims 1-3, comprising the following steps: (1) Add template agent and catalyst to water, stir, and then add tetraethyl silicate and oil phase mixed solution and co-solvent in sequence. After heating and reaction, centrifuge, wash, dry and calcinate to obtain wrinkled mesoporous nanomaterials. (2) Disperse the wrinkled mesoporous nanomaterial in water, add silane coupling agent to carry out modification reaction, and obtain modified wrinkled mesoporous nanomaterial; disperse the modified wrinkled mesoporous nanomaterial in water, add functional monomer, carry out graft polymerization reaction in the presence of initiator, and obtain functionalized wrinkled mesoporous nanomaterial after separation, washing and drying. (3) The hydrophilic monomer, betaine-type functional monomer and hydrophobic monomer are copolymerized in water in the presence of an initiator in the presence of a surfactant. After precipitation, drying and granulation, a betaine-type hydrophobic associative polymer is obtained. (4) The functionalized wrinkled mesoporous nanomaterial is dispersed in water to form a suspension, the betaine-type hydrophobic associative polymer is dissolved in water to form a polymer solution, and the polymer solution is added to the suspension and mixed to obtain the active wrinkled mesoporous nano-oil displacement system.

5. The preparation method according to claim 4, characterized in that: The conditions in step (1) are as follows: The template agent is selected from one or more of hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, hexadecylpyridine bromide, and hexadecylpyridine chloride. The template agent has a mass fraction of 1-5%; The catalyst is selected from one or more of ammonia, urea, methylamine, n-propylamine, ethylenediamine, 1,2-propanediamine, 1,3-propanediamine, ethanolamine, formamide, and acetamide. The mass fraction of the catalyst is 1-4%; The oil phase is selected from one or more of benzene, toluene, p-xylene, styrene, chlorobenzene, cyclohexane, n-hexane, n-octane, and decane; The mass fraction of the tetraethyl silicate is 5-40%; The co-solvent is selected from one or more of methanol, ethanol, ethylene glycol, isopropanol, n-butanol, n-pentanol, and octanol; The mass fraction of the co-solvent is 1-10%; The reaction temperature is 60-100℃; The reaction time is 1-15 h.

6. The preparation method according to claim 4 or 5, characterized in that: The conditions in step (2) are as follows: The mass fraction of the wrinkled mesoporous nanomaterial is 0.05-0.3%; The silane coupling agent is selected from one of vinyltris(β-methoxyethoxy)silane, vinyltrimethoxysilane, vinyltriethoxysilane, and γ-methacryloyloxypropyltrimethoxysilane; The mass fraction of the silane coupling agent is 1-3%; The temperature of the modification reaction is 60-100℃; The modification reaction takes 0.5-5 hours; The modified wrinkled mesoporous nanomaterial has a mass fraction of 0.05-0.25%; The functional monomer is selected from one of N,N'-dimethyl(methacrylamide ethyl)ammonium propanesulfonate, N,N'-dimethyl(methacryloyloxyethyl)ammonium propanesulfonate, and 3-(N-allyl-N-methylamino)propane-1-sulfonate, preferably N,N'-dimethyl(methacryloyloxyethyl)ammonium propanesulfonate. The mass fraction of the functional monomer is 0.05-0.15%; The initiator has a mass fraction of 0.01-0.05%; The temperature of the graft polymerization reaction is 30-60℃; The graft polymerization reaction takes 1-6 hours.

7. The preparation method according to any one of claims 4-6, characterized in that: The conditions in step (3) are as follows: The hydrophilic monomer is selected from one of acrylamide, methacrylamide, N,N-dimethylacrylamide, and N,N'-methylenebisacrylamide; The betaine-type functional monomer is selected from one of N,N'-dimethyl(methacrylamide ethyl)ammonium propanesulfonate, N,N'-dimethyl(methacryloyloxyethyl)ammonium propanesulfonate, and 3-(N-allyl-N-methylamino)propane-1-sulfonate; The hydrophobic monomer has a carbon chain length of C8-C9. 18 The acrylate hydrophobic monomer is preferably selected from one of n-octyl acrylate, decyl acrylate, tetradecyl acrylate, hexadecyl acrylate, octadecyl acrylate, undecyl methacrylate, lauryl methacrylate, and octadecyl methacrylate. The molar ratio of the hydrophilic monomer, betaine-type functional monomer, and hydrophobic monomer is (80-95):(5-20):(0.5-1.5); The total mass fraction of the monomer is 15-35%; The surfactant is selected from one of sodium dodecyl sulfonate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, polyethylene glycol octylphenyl ether, and polyoxyethylene sorbitan fatty acid ester. The surfactant has a mass fraction of 1-5%; The initiator has a mass fraction of 0.01-0.04%; The copolymerization reaction is carried out at a temperature of 30-80℃; The copolymerization reaction takes 2-6 hours.

8. A functionalized wrinkled mesoporous nanomaterial comprising a wrinkled mesoporous silica matrix and betaine-type functional monomer segments grafted onto the surface of the matrix; The surface of the matrix exhibits a lamellar or layered folded morphology, with isolated and unconnected pores, and the pore structure is radial; the particle size of the matrix is ​​50-300 nm, and the specific surface area is 300-1100 m². 2 ·g -1 The pore volume is 0.5-2 cm³. 3 ·g -1 The pore length of the mesopores is 10-200 nm; The betaine-type functional monomer is selected from N,N'-dimethyl(methacrylamide ethyl)ammonium propanesulfonate, N,N'-dimethyl(methacryloyloxyethyl)ammonium propanesulfonate, or 3-(N-allyl-N-methylamino)propane-1-sulfonate.

9. A betaine-type hydrophobic associative polymer comprising structural unit A, structural unit B and structural unit C; The structural unit A is derived from a hydrophilic monomer, which is selected from acrylamide, methacrylamide, N,N-dimethylacrylamide or N,N'-methylenebisacrylamide; The structural unit B is derived from a betaine-type functional monomer, which is selected from N,N'-dimethyl(methacrylamide ethyl)ammonium propanesulfonate, N,N'-dimethyl(methacryloyloxyethyl)ammonium propanesulfonate or 3-(N-allyl-N-methylamino)propane-1-sulfonate; The structural unit C is derived from a hydrophobic monomer, which has a carbon chain length of C8~C8. 18 acrylate hydrophobic monomers; The molar ratio of structural unit A, structural unit B and structural unit C is (80-95):(5-20):(0.5-1.5).

10. The application of the temperature-resistant and salt-resistant active wrinkled mesoporous nano-oil displacement system according to any one of claims 1-3, the functionalized wrinkled mesoporous nanomaterial according to claim 8, or the betaine-type hydrophobic associating polymer according to claim 9 in oil displacement and enhanced oil recovery in high-temperature and high-salinity oil reservoirs.